IMPACT OF MENOPAUSE ON QUALITY OF LIFE AMONG INDIAN WOMEN - Kaur, Navdeep; Kaur, Ravinder (LIFE: International Journal of Health and Life-Sciences, 2020)
Research Objectives: The objective of the study was to assess the impact of menopause on the quality of life of Indian women. Methodology: 155 women, in the age range of 40 to 60 years, from various parts of India were included in the study based on inclusion criteria (mentally oriented women not using hormonal replacement therapy, without history of hysterectomy and medical conditions like hypertension, diabetes and thyroid problems). Menopause-specific Quality of Life (MENQOL) questionnaire was used to assess the presence of symptoms in vasomotor, psychosocial, physical and sexual domains. Menopausal status was categorized as Late perimenopausal, Early perimenopausal, Premenopausal and postmenopausal. Findings: Descriptive statistics was used to analyze the data. The average age of participants was 50.7 years with average BMI of 25.9. A largest no. of women were in the postmenopausal status (n=115), followed by premenopausal (n=19), early perimenopausal (15) and late perimenopausal (n=6) status. Most common symptom in vasomotor domain was sweating (38.06%), in psychosocial domain feeling anxious (25.80%) and depressed (25.16), in physical domain decrease in physical strength (49.67%), feeling tired (48.38%), lack of energy (47.74%), low backache (47.74%), aching in muscles and joints (46.45%) whereas in sexual domain mild vaginal dryness during intercourse (30%) and change in sexual desire (28.67%). Research Outcomes: The menopausal symptoms lasted many years after the cessation of menstruation. 25-50% of prevalence rate in various domains indicates a need to adopt multidimensional approach, for the better management of menopausal symptoms. Future Scope: Future study may be carried out with equal sample size in all the categories of menopausal status to identify the relationship between the severity of menopausal symptoms and the menopause status.